THE EFFECT OF SEVERAL DESINFECTANTS ON THE SPORULATION OF THE ERIMERIA TENELLA OOCYST - Eryl Sri Rohayati; Julianti Darjono; Wisnu Nurcahyo (Jurnal Sain Veteriner, 1999)
A research has been conducted to evaluate the effect of certain desinfectants on the speculation of the Eimerla tenclla oocysts.In this research in vitro methode has been used. This research used oocysts Eimeria tenella which have not yet Sporulated. 6 kinds of disinfectants and water as control. These desinfectants were used in the research namely : Lysol, Creolin. Kalium Jodida (KJ). Formalin, Bromoquod and Ca (OH)2.The oocysts which have not yet sporulation were imerted in these desinfectants. The duration of liners ion at each treatment was succescively 10 minutes. 20 minutes and 30 minutes. The desinfectants concentration used is of three degree of strength, in the following proportion = 1:2:4.The data colected was the percentage of oocystys which have sporulated 24 hours, 48 hours and 72 hours, after treatment. The data was analyzed with the Split Plot method (Gill. 1978).The result of research showed that each desinfectant had a different effect on the percentage of the oocyst sporulation (P < 0,01) . Bromoquod was found to be the best desinfectant, and the others were in this following order = Creolin. KJ, Water, Lysol. CafQHJn and formalin. The Concentration was also found significantly effective (P < 0,6) in suppressing the sporulation of the oocysts. Creolin concentration of the 4tri strength was found to be the best desinfectant and the others were in this following order : water. KJ. Bromoquod, Lysol, Ca(OH)£ and formalin. The duration of imersion had no significant influence